PENERAPAN E-GOVERNMENT DALAM PELAYANAN ADMINISTRASI KEPEGAWAIAN: STUDI DI BKPSDM KABUPATEN SUMENEP - Syafriyani, Ida; Zaituna, Yuli Putri (Department of Public Administration, Universitas Negeri Surabaya, 2018)
Sumenep Government has implemented E-Government in staffing administration services, in the form of managing the staffing management information system (SIMPEG) by creating an online-based service system. SIMPEG was inaugurated since 2013 by the Human Resources and Human Resources Development Agency. The aims to make it easier to manage employee data. The problems is how the application of E-Government in the service of personnel administration in the human resources and human resource development agency of Sumenep Regency. The research objective is to determine the application of E-Government in the service of personnel administration in the human resources and human resource?development of Sumenep. Analysis method uses a descriptive qualitative approach, which is the focus of this research are: 1) E-leadership, 2) information network infrastructure, 3) network management, and 4)?community and human resources. The subjects of this study were key informants, main, and supporting informants, data collection techniques by interviewing, observing, and documenting, with data analysis?namely, data reduction, data display, and data verification. Based on the results shows that in general the application of E-Government in the form of SIMPEG has been well applied. Supported by E-Leadership, information management and information network infrastructure that has provided such as the presence of optical servers and features that function to store data and provide a data management network for personnel. However, there are obstacles that hinder the implementation of E-Government, which lies in the data management officials in each OPD who still lack understanding of information technology.?